2020
DOI: 10.3390/su12072694
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Embedded Global Value Chain on Technical Complexity of Industry Export—An Empirical Study Based on China’s Equipment Manufacturing Industry Panel

Abstract: This study uses the World Input–Output Database (WIOD) to construct an export technical complexity index based on the effective elimination of imported foreign technology. The panel data of China’s equipment manufacturing industry from 2000 to 2014 are used as a sample, and the instrumental variable method is used to test the impact of the embedded global value chain on the technical complexity of industry exports. The impacts of different embedding time periods and different embedding methods on the technical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…It can be seen from columns (1)-(3) and (4)-(6) that GVC participation has a more positive moderating effect on enterprises with low and medium productivity. The results show that when GVC participation is high, manufacturing servitization significantly promotes the export technological sophistication of low-efficiency enterprises, which is similar to previous literature conclusions [ 65 , 68 ]. The possible explanation is that there are a large number of processing trade enterprises engaged in low value-added business in China, and their productivity can not accurately reflect their international competitiveness, that is, there is a "productivity paradox" phenomenon.…”
Section: Expansibility Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…It can be seen from columns (1)-(3) and (4)-(6) that GVC participation has a more positive moderating effect on enterprises with low and medium productivity. The results show that when GVC participation is high, manufacturing servitization significantly promotes the export technological sophistication of low-efficiency enterprises, which is similar to previous literature conclusions [ 65 , 68 ]. The possible explanation is that there are a large number of processing trade enterprises engaged in low value-added business in China, and their productivity can not accurately reflect their international competitiveness, that is, there is a "productivity paradox" phenomenon.…”
Section: Expansibility Analysissupporting
confidence: 90%
“…The existing research shows that manufacturing servitization plays an important role in promoting the international competitiveness of enterprises when the global value chain has deeply participated [ 64 , 65 ]. However, there is still little literature on the economic effects of GVC (global value chain) participation based on the data of micro-enterprises, especially the further research on the combination of the new production division system of GVC and the servitization of the manufacturing industry.…”
Section: Expansibility Analysismentioning
confidence: 99%
“…Regarding the China-US trade, in 2014, China exported USD 468 billion in goods to the United States, 41% on final goods (FG), and 59% as intermediate parts and components (IPCs). A large share of IPCs is shipped to the US via indirect partners as it is well documented [5,17,18]. The largest exports from China to the US originate from computers, electronic, and electrical equipment, equal to USD 158 billion in 2014.…”
Section: Resultsmentioning
confidence: 99%
“…Since 2018, trade tensions between the United States (US) and China have escalated, amidst concerns of currency manipulation [1], state subsidies [2], trade imbalances [3,4], re-launching of export strategies [5], intellectual property issues [6], national security [7], and many others [8]. Increased US tariffs on Chinese imports were straightaway responded with counter tariffs from China on at least three big 'special tariffs' waves.…”
Section: Introductionmentioning
confidence: 99%
“…At a significance level of 0.01, H3a, and H3b passed the test. Li et al (2020) found that establishing the GVC can improve the export technical complexity of the equipment-manufacturing industry, and with the promotion of domestic openness and industry R and D investment conditions, this improvement is likely to be healthy. Through interviews with executives of Chinese business groups and its subsidiaries, it was found that in order to improve the companie's overseas low carbon products and technology marketing activities, the companies were strengthening their marketing management innovations.…”
Section: Direct Effect Testingmentioning
confidence: 99%